Are coordinative abilities impaired during adolescence in academy soccer? - Hemmings, R. J.; Maloney, S. J. (Journal of Sports Sciences, 2025)
The current study sought to compare single leg (SL) landing and cutting mechanics within a cohort of youth footballers. A secondary aim was to examine how task complexity modulates the relationship between maturation and performance. Thirty-nine soccer players from an English football academy were categorised as pre-, circa- and post-peak height velocity (PHV). As part of routine club testing, players performed 1) bilateral and SL jumps (countermovement jump (CMJ) and 10/5 rebound jump tests), 2) speed (30-m sprint), and 3) change of direction (COD; 505 test and 45° cut) assessments. Landing (LESS score) and cutting mechanics (CMAS score) were determined during SL CMJ and 45° cuts, respectively. Differences in landing mechanics were not observed between groups. However, large effect sizes indicated that CMAS scores were lower in the post-PHV group versus pre- and circa-PHV groups, indicative of a favourable cutting technique. The circa-PHV group outperformed the pre-PHV group in the `simpler` bilateral CMJ and linear sprint assessments, but not in the SL CMJ, 10/5 or COD assessments. The observed variability between participants in the circa-PHV period could be interpreted by changes in coordinative abilities. It is possible that athletes may require closer monitoring and possible training modification during this phase.